Prospective Evaluation of the Relationship Between Mechanical Stability and Response to Palliative Radiotherapy for Symptomatic Spinal Metastases. (August 2017) - van der Velden, Joanne M.; Versteeg, Anne L.; Verkooijen, Helena M.; Fisher, Charles G.; Chow, Edward; Oner, F. Cumhur; van Vulpen, Marco; Weir, Lorna; Verlaan, Jorrit‐Jan
Abstract: Background: A substantial number of patients with spinal metastases experience no treatment effect from palliative radiotherapy. Mechanical spinal instability, due to metastatic disease, could be associated with failed pain control following radiotherapy. This study investigates the relationship between the degree of spinal instability, as defined by the Spinal Instability Neoplastic Score (SINS), and response to radiotherapy in patients with symptomatic spinal metastases in a multi‐institutional cohort. Methods and Materials: The SINS of 155 patients with painful thoracic, lumbar, or lumbosacral metastases from two tertiary hospitals was calculated using images from radiotherapy planning CT scans. Patient‐reported pain response, available for 124 patients, was prospectively assessed. Pain response was categorized, according to international guidelines, as complete, partial, indeterminate, or progression of pain. The association between SINS and pain response was estimated by multivariable logistic regression analysis, correcting for predetermined clinical variables. Results: Of the 124 patients, 16 patients experienced a complete response and 65 patients experienced a partial response. Spinal Instability Neoplastic Score was associated with a complete pain response (adjusted odds‐radio [ORadj] 0.78; 95% confidence interval [CI] 0.62–0.98), but not with an overall pain response (ORadj 0.94; 95% CI 0.81–1.10). Conclusions: A lower SINS, indicating spinal stability, is associated with a complete pain response to radiotherapy. This supports the hypothesis that pain resulting from mechanical spinal instability responds less well to radiotherapy compared with pain from local tumor activity. No association could be determined between SINS and an overall pain response, which might indicate that this referral tool is not yet optimal for prediction of treatment outcome. Implications for Practice: Patients with stable painful spinal metastases, as indicated by a Spinal Instability Neoplastic Score (SINS) of 6 or lower, can effectively be treated with palliative external beam radiotherapy. The majority of patients with (impending) spinal instability, as indicated by a SINS score of 7 or higher, will achieve a (partial) response after palliative radiotherapy; however, some patients might require surgical intervention. Therefore, it is recommended to refer patients with a SINS score of 7 or higher to a spine surgeon to evaluate the need for surgical intervention. Abstract : This study investigated the relationship between the degree of spinal instability, as defined by the Spinal Instability Neooplastic Score, and response to radiotherapy in patients with symptomatic spinal metastases in a multi‐institutional cohort.